IDENTIFIKASI DAN EFISIENSI KINERJA RANTAI PASOK IKAN LELE DI CIMANGGU FISH CENTER KABUPATEN CIANJUR - Sri Agustina Wulandari; Murti Widyaningsih; M.Nuruddin Subhan (JIMP : Jurnal Ilmiah Manajemen Pancasila, 2026)
This research aims to analyze the influence of distribution channels and marketing efficiency on the supply chain performance at Cimanggu Fish Center, Cianjur Regency. A quantitative approach was employed using marketing margin analysis, farmer’s share, benefit-cost ratio, and the Analytical Hierarchy Process (AHP) method. The findings indicate that shorter distribution channels have a positive impact on distribution cost efficiency and overall supply chain performance. Marketing costs increases farmer’s profitability. Simultaneously, both distribution channels and marketing efficiency contribute positively to supply chain performance, with simplified distribution flows and efficient marketing serving as key drivers of improved performance. These findings suggest the need for more integrated and strategic supply chain management to support the sustainability of catfis farmingenterprises.